Using chaos synchronization to estimate the largest lyapunov exponent of nonsmooth systems - Andrzej Stefanski; Tomasz kapitaniak (Discrete Dynamics in Nature and Society)
We describe the method of estimation of the largest Lyapunov exponent of nonsmooth dynamical systems using the properties of chaos synchronization. The method is based on the coupling of two identical dynamical systems and is tested on two examples of Duffing oscillator: (i) with added dry friction, (ii) with impacts.